Associations of cord blood meta-inflammation and vitamin D with neurodevelopmental delay: A prospective birth cohort study in China - Wang, Peng; Wu, Lin; Yin, Wan-jun; Tao, Rui-xue; Zhang, Ying; Li, Pei-pei; Jiang, Xiao-min; Shao, Zi-yu; Zhu, Peng (Frontiers in Immunology, 2023)
AIM To estimate the associations of cord meta-inflammatory markers with neurodevelopment, including the potential impact of cord blood vitamin D levels. METHOD The prospective cohort study comprised 7198 participants based on the Maternal & Infants Health in Hefei study. Cord blood C-peptide, high-sensitive C-reactive protein (hsCRP), high-density lipoprotein-cholesterol, low-density lipoprotein-cholesterol, total cholesterol, triglycerides and 25(OH)D levels were measured. The Gesell Developmental Schedules were used to assess neurodevelopmental outcomes in offspring. RESULTS After adjusting potential confounders, per quartile increase in cord blood 25(OH)D concentrations was associated with a decreased risk of neurodevelopmental delay [hazard ratios (HR) 0.65 (95% CI 0.57, 0.74)]. Conversely, significant positive associations with cord blood serum C-peptide levels above the 90th percentile [HR 2.38 (95% CI 1.81, 3.13)] and higher levels of cord hsCRP (per quartile increase) [HR 1.18 (95% CI 1.01, 1.37)] with neurodevelopmental delay were observed. These associations could vary by quartiles of cord blood 25(OH)D levels: the adjusted HRs in neurodevelopmental delay comparing children with vs without hyperinsulinemia were 1.28 (95% CI: 1.03, 1.59) for quartiles 1 (lowest), and 1.06 (95% CI: 0.78, 1.44) for quartile 4 (highest). Conclusions Immune activation and metabolic abnormalities in fetal circulation were associated with neurodevelopmental delay in offspring, which could be attenuated by higher cord blood 25(OH)D levels in a dose-response manner.